Anatomy of a Robot : Literature, Cinema, and the Cultural Work of Artificial People - Kakoudaki, Despina (Book collections on Project MUSE., 2014)
Why do we find artificial people fascinating? Drawing from a rich fictional and cinematic tradition, Anatomy of a Robot explores the political and textual implications of our perennial projections of humanity onto figures such as robots, androids, cyborgs, and automata. In an engaging, sophisticated, and accessible presentation, Despina Kakoudaki argues that, in their narrative and cultural deployment, artificial people demarcate what it means to be human. They perform this function by offering us a non-human version of ourselves as a site of investigation. Artificial people teach us that bein.